Mapping the Trajectory of Islamic Education Research: A Bibliometric Analysis - Widyaningrum, Nyimas Esti; Inayati, Nurul Latifatul; Apriantoro, Muhamad Subhi; Ashfahany, Afief El; Nurlita, Eta (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
This study aims to describe the mapping of the development and direction of research on the development of Islamic education in publications indexed by the Scopus database. This study uses bibliometric analysis techniques to explore all journals indexed in the Scopus database on the development of Islamic education from 1974 to 2022/2023. The data obtained is analyzed using Excel and R/R-Studio. VOSviewer visually analyses the simultaneous occurrence of keywords and document citations. The author found 656 publications that fit the function, subject, and criteria set. The results of this study showed an annual growth rate of 6.69%. The first position is held by the author named Bensaid, B., followed by Avest, I.T., and Nor, M.R.M. The country that produces many scientific publications on Islamic education development is the State of Indonesia, with as many as 198 documents. The bibliometric analysis performed was limited to Scopus data. Other national and international databases should have been considered in the study. This study presents a brief overview of the literature accessible to researchers in developmental fields and provides recommendations for future research.